miRNA-seq and clinical evaluation in multiple myeloma: miR-181a overexpression predicts short-term disease progression and poor post-treatment outcome - Papadimitriou, M. A.; Papanota, A. M.; Adamopoulos, P.G.; Pilala, K. M.; Liacos, C. I.; Malandrakis, P.; Mavrianou-Koutsoukou, N.; Patseas, D.; Eleutherakis-Papaiakovou, E.; Gavriatopoulou, M.; Kastritis, E.; Avgeris, M.; et al. (British Journal of Cancer, 2022)
BACKGROUND: Despite significant advances in multiple myeloma (MM) therapy, disease relapse and treatment resistance remain major obstacles in clinical management. Herein, we have studied the clinical utility of miRNAs in improving patients' risk-stratification and prognosis. METHODS: miRNA-seq was performed in CD138+ plasma cells of MM, smoldering multiple myeloma (sMM) and monoclonal gammopathy of undetermined significance (MGUS) patients. The screening MM cohort consisted of 138 patients. miRNA levels of CD138+ plasma cells were quantified by RT-qPCR following 3'-end RNA polyadenylation. Disease progression and patients' death were used as clinical end-point events. Internal validation was conducted by bootstrap analysis. Clinical net benefit on disease prognosis was assessed by decision curve analysis. Kruykov et al. 2016 served as validation cohort (n = 151). RESULTS: miRNA-seq highlighted miR-181a to be upregulated in MM vs. sMM/MGUS, and R-ISS III vs. I patients. Screening and validation cohorts confirmed the significantly higher risk for short-term progression and worse survival of the patients overexpressing miR-181a. Multivariate models integrating miR-181a with disease established markers led to superior risk-stratification and clinical benefit for MM prognosis. CONCLUSIONS: CD138+ overexpression of miR-181a was strongly correlated with inferior disease outcome and contributed to superior prediction of MM patients early progression, supporting personalised prognosis and treatment decisions.